2017
DOI: 10.1002/ange.201703279
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Dictyodendrins by the Gold‐Catalyzed Cascade Cyclization of Conjugated Diynes with Pyrroles

Abstract: In total and formal syntheses of dictyodendrins B, C, E, and F, the key step involved the direct construction of the pyrrolo[2,3‐c]carbazole core by the gold‐catalyzed annulation of a conjugated diyne with a pyrrole to form three bonds and two aromatic rings. The subsequent introduction of substituents at the C1 (Suzuki–Miyaura coupling), C2 (addition to an aldehyde), N3 (alkylation), and C5 positions (Ullman coupling) provided divergent access to dictyodendrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…The molecular structure of 9 t was inferred from X-ray diffraction analysis of its analogue 9 u. [19] Based on these results and the reported literature, [9][10][11][12][13][14][15] a tentative reaction mechanism was proposed for the generation of polysubstituted quinolines, which is shown in Scheme 7. Initially, 6-endo-dig cyclization of the Ag(I)-activated alkyne moiety with tethered azide formed intermediate I, which further led to aimino silver carbene species II after extrusion of N 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular structure of 9 t was inferred from X-ray diffraction analysis of its analogue 9 u. [19] Based on these results and the reported literature, [9][10][11][12][13][14][15] a tentative reaction mechanism was proposed for the generation of polysubstituted quinolines, which is shown in Scheme 7. Initially, 6-endo-dig cyclization of the Ag(I)-activated alkyne moiety with tethered azide formed intermediate I, which further led to aimino silver carbene species II after extrusion of N 2 .…”
Section: Resultsmentioning
confidence: 99%
“…To our delight, the yields of 3 a were improved dramatically when the reaction was promoted by silver catalysts. Examination of different silver catalysts at different temperatures (entry [8][9][10][11][12][13] revealed that AgSbF 6 gave the best yield at 20 8C (entry 11, 85% yield). The molecular structure of 3 a was inferred from X-ray diffraction analysis of its analogue 3 n. [19] With the optimal reaction conditions established, the substrate scope of azide alkynes with various substituted aromatic nucleus was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, as we envisioned in Scheme , we decided to test the more challenging pyrrole substrate in order to gauge the full capability of this interesting method ,. We found that under slightly modified reaction conditions, the synthetically valuable symmetric densely substituted and hydroxyl containing carbazoles were formed in moderate yields (Table ).…”
Section: Figurementioning
confidence: 99%
“…[4] Among these approaches, the gold-catalyzed alkyne cyclization with tethered azide, which is firstly reported by Toste and coworkers, [5,6] has provided general access to Nheterocycles via corresponding α-iminocarbene intermediates under a mild and neutral conditions (Scheme 1a). Later, this useful method has been further studied by Zhang, [7] Gagosz, [8] Ohno, [9] Ye, [10] us, [11] and others [12] for the preparation of pyrrole or indole derivatives with structural diversity.…”
Section: Introductionmentioning
confidence: 99%